Integration of Servant Leadership and Psychological Factors on Teachers' OCB - Nur Amega Setiawati; Soewarto Hardhienata; Herfina (International Journal of Technology and Education Research, 2025)
Teachers’ Organizational Citizenship Behavior (OCB) plays a crucial role in enhancing school effectiveness and the quality of educational services, particularly in private vocational high schools that face increasing performance and competitiveness demands. However, the lack of extra-role behavior among teachers remains a persistent challenge. This study aims to examine the effects of Servant Leadership and teachers’ psychological factors on Organizational Citizenship Behavior (OCB) among teachers in private vocational high schools in West Jakarta, both directly and indirectly. This research employed a quantitative approach using a survey method. The population consisted of 1,119 permanent teachers from A-accredited private vocational high schools in West Jakarta, with a sample of 199 teachers selected through proportional random sampling. Data were collected using validated and reliable structured questionnaires and analyzed using Path Analysis to examine causal relationships among variables. The findings indicate that Servant Leadership and psychological factors have a positive and significant effect on teachers’ OCB, both partially and simultaneously. Psychological factors emerge as a key variable that strengthens the influence of Servant Leadership on teachers’ extra-role behavior. This study contributes theoretically to the development of OCB research within educational leadership studies and provides practical implications for school management in designing strategies to enhance teachers’ performance through the strengthening of servant leadership practices and the management of teachers’ psychological conditions.